Pathophysiological role of RhoA/Rho-kinase under oxygen-glucose deprivation/reperfusion and hyperglycaemia - Srivastava, Kirtiman (2013)
Introduction: Oxygen-glucose deprivation (OGD)±reperfusion and hyperglycaemia exacerbate the ischaemic cerebral injuries during or after a stroke. The key biochemical events associated with these pathologies include excessive cytoskeletal remodelling, modulation of tight junction proteins and the induction of oxidative stress. Recently, the overactivities of protein kinase C (PKC), RhoA/Rho-kinase, and pro-oxidant NADPH oxidase have been shown to account for the development of these events and the consequent disruption of human blood-brain barrier (BBB) integrity. Objectives: This thesis focused on the putative roles of RhoA/Rho-kinase signalling in OGD and OGD+reperfusion-evoked modulation of cytoskeletal remodelling, tight junction proteins and oxidative stress in human brain microvascular endothelial cells (HBMEC). The effects of hyperglycaemia-mediated PKC overactivities in modulating the RhoA/Rho-kinase pathway with reference to the aforementioned parameters i.e. cytoskeletal remodelling and tight junction protein expression and localisation have also been the focus of this thesis. Methods: For the OGD studies, the HBMEC were exposed to normoxia (controls), OGD (4, 20 hours) alone and followed by reperfusion (20 hours). The HBMEC-human astrocyte (HA) cocultures were established to mimic human BBB before exposing them to the experimental conditions. The integrity and function of HBMEC-HA cocultures were measured by transendothelial electrical resistance (TEER) and flux of permeability markers sodium fluorescein (NaF) and Evan’s blue-labelled albumin (EBA), respectively. For the hyperglycaemia studies, the HBMEC monolayers and the cocultures were exposed to normoglycaemia (5.5 mM D-glucose), hyperglycaemia (25 mM D-glucose), and hyperglycaemia with inhibitors of Rho-kinase, PKC, PKC-α, PKC-β, PKC-βII, PKC-δ; and the BBB integrity and function were measured by the TEER and flux studies, respectively. Fold differences in the protein expression or activity of RhoA, Rho-kinase-2, mono- and di-phosphorylated myosin light chain-2 (MLC2), total MLC2, gp91-phox (a pivotal NADPH oxidase subunit), catalase, occludin, claudin-5, zonula occludens-1 (ZO-1), β-catenin, and vinculin were either measured by in-cell or ordinary Western analyses. Results from the OGD studies: OGD compromised the barrier integrity as observed by decreases in TEER values and concomitant increases in flux of EBA and NaF across the cocultures. Transfection of HBMEC with constitutively active RhoA also decreased the TEER and increased the NaF paracellular permeability, whereas inactivation of RhoA by anti-RhoA-IgG electroporation exerted barrier protective effects. Moreover, OGD alone and after constitutively active RhoA transfection introduced stress fibres in HBMEC, which were abrogated by inactivation of RhoA and the specific inhibition of its main effector Rho-kinase by Y-27632. In addition, dramatic increases in the protein expressions of RhoA-GTP, Rho-kinase-2, gp91-phox, and antioxidant catalase were observed in HBMEC exposed to OGD+reperfusion conditions. These along with increases in the NADPH oxidase activity and total superoxide anion levels confirmed the oxidative stress in HBMEC under these experimental conditions. A marked rise in the protein expressions of claudin-5 and β-catenin observed after OGD (20 hours) alone and followed by reperfusion may represent the effects of oxidative stress on tight and adherens junction proteins stability, respectively. These results also concurred with marked decreases in TEER and concomitant increases in the flux of EBA across the in vitro models of human BBB exposed to OGD±reperfusion conditions when compared with the controls. Cotreatment with Y-27632 under OGD±reperfusion normalised the protein expressions of RhoA, Rho-kinase-2, gp91-phox, claudin-5, catalase; activities of RhoA and NADPH oxidase; and total superoxide anions levels, alongside improving the expression of occludin and the coculture integrity under the OGD±reperfusion conditions. Results from the hyperglycaemia studies: Hyperglycaemia also increased RhoA-GTP, Rho-kinase-2, mono- and di-phosphorylated MLC2 protein levels and total PKC activity. These changes were consistent with the actin stress fibre formations, ZO-1 and occludin redistribution from HBMEC periphery. Hyperglycaemia-mediated endothelial-barrier dysfunction was further characterised by reduction in TEER and elevation in flux of EBA. Glucose normalisation, RhoA neutralisation by anti-RhoA-IgG electroporation and Rho-kinase-2 inhibition by Y-27632 normalised all abovementioned protein expressions, restored actin and tight junction protein localisations and barrier integrity. Cotreatment of HBMEC with hyperglycaemia and a general PKC inhibitor namely, bisindolylmaleimide-I normalised the Rho-kinase-2, mono- and di-phosphorylated MLC2 levels. Moreover, specific inhibitors of PKC-α (Ro-32-0432), PKC-β (LY333531), PKC-βII (CGP53353) attenuated the PKC overactivity, normalised all protein expressions, restored actin localisation and improved barrier integrity. In addition, the PKC-α and PKC-β siRNA transfections mimicked the effects of the specific inhibitors and attenuated the hyperglycaemia-evoked RhoA-GTP, mono- and di-phosphorylated MLC2 protein levels and stress fibre formations. Conclusions: The RhoA/Rho-kinase overactivities compromise the endothelial-barrier integrity, in part, by modulating the cytoskeletal remodelling and inducing the NADPH oxidase-evoked oxidative stress under OGD±reperfusion pathology. Moreover, hyperglycaemia-mediated increases in PKC-α and PKC-β activities exacerbate the endothelial-barrier dysfunction by modulating RhoA/Rho-kinase signalling pathway. Summary: These findings support the hypothesis that OGD±reperfusion and hyperglycaemia perturb BBB integrity through regulation of RhoA/Rho-kinase activity and modulation of cytoskeletal reorganisation, oxidative stress and tight junction protein expressions or localisations.